Global coffee and cultural change in modern Japan - Grinshpun, Helena. (Abingdon, Oxon ; New York, NY)
1 online resource
Keywords: This book explores the impact in Japan of the rise of global coffee chains and the associated coffee culture. Based on extensive original research, the book discusses the cultural context of Japan, where tea-drinking has been culturally important, reports on the emergence of the new coffee shop consumer experience, and reflects on the link between consumption and identity, on cultural fantasies about modern, Western, or global lifestyles, on the effects of global standardization, and on much more.